Effect of support for alcohol-hydrocarbon synthesis from syngas in Cu-based catalyst - Yeon, Sun-Hwa; Shin, Dae-Hyun; Nho, Nam-Sun; Shin, Kyoung-Hee; Jin, Chang-Soo; Nam, Sung-Chan (The Korean journal of chemical engineering, 2013)
Effects of a Cu-based catalyst on the catalytic performance in alcohol-hydrocarbon synthesis from syngas have been investigated, using various supports. Under the different porosities of three supports (zinc oxide, activation carbon, and titanium dioxide), whereas Cu/ZnO produces one liquid phase of major mixed alcohols, Cu/AC and Cu/TiO 2 create two phases, alcohol (∼75%) and hydrocarbon (∼25%). X-ray diffraction shows that CuO impregnated on supports undergoes a complete reduction of metallic copper Cu 0 , which is the real active phase in the catalytic process. The Cu/TiO 2 catalyst showed the highest ethanol composition in a mixed alcohol phase under GHSV 18,000 h −1 , 30 bar, and 300 °C.